Pengembangan Media Pembelajaran Visual Untuk Meningkatkan Pemahaman Konsep Siswa - Wahidin, Wahidin (Jurnal Ilmiah Edukatif, 2025)
This study aims to explore the utilization of visual learning media in improving students' conceptual understanding, using a qualitative approach through research and development (R&D). The main focus of this research is on visual elements such as images, graphs, videos, and other visual aids used to accelerate students' comprehension of the subject matter. The research informants include 4 school principals, 10 teachers, 10 parents, and 10 eighth-grade students from 4 public junior high schools in Kapuas Regency. Data collection was conducted through semi-structured interviews, direct observations, surveys, and documentation. To analyze the data, a triangulation approach was employed to ensure the accuracy of the research findings. The research findings indicate that the use of visual learning media is effective in enhancing students' understanding of abstract concepts, increasing student engagement, and stimulating creativity. In addition, visual media also contributes positively to understanding lessons at home. Adequate infrastructure support and the development of appropriate media are crucial for the successful implementation of visual media in the learning process.